2012
DOI: 10.2507/ijsimm11(2)2.202
|View full text |Cite
|
Sign up to set email alerts
|

Design of modern hydraulic tank using fluid flow simulation

Abstract: Hydraulic power units are one of the most commonly used power sources in industry. The progress in recent years has offered high efficiency and reliable hydraulic components, yet the hydraulic tank design is often neglected part of the development.The paper presents the development of industrial 400 litre hydraulic tank. In order to reduce oil swirling and improve stability of fluid flow, CFD simulations of oil flow inside hydraulic tank were made. Several variations of new hydraulic tank designs are compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Some research about solenoid valve for valve-control coupling provides a good basis for this study [9] to [11]. Other related research about valve design [12], simulation [13] and improvement [14] is also encouraging. However, the application requirement of the solenoid control valve group is stricter in some difficult operating environments.…”
Section: Introductionmentioning
confidence: 84%
“…Some research about solenoid valve for valve-control coupling provides a good basis for this study [9] to [11]. Other related research about valve design [12], simulation [13] and improvement [14] is also encouraging. However, the application requirement of the solenoid control valve group is stricter in some difficult operating environments.…”
Section: Introductionmentioning
confidence: 84%
“…The results of meshing are shown in Figure 4.4 and presented in Table 4.2. More information on the study can be found in literature [72], [70]. …”
Section: On-line Condition Monitoring and Evaluation Of Remaining Usementioning
confidence: 99%
“…The first approach, which is based on an adequate tracking and intelligent closed loop control using adaptive feedback systems, satisfies most of the practical technical requirements for the quality of the dynamic behaviour of the hydraulic system [1] and [2]. The other approaches, such as direct numerical simulation using an immersed-boundary method [3] or three dimensional CFD analysis [4] and [5], provide more flexibility and reveal an opportunity for the development of new mechanical design solutions.…”
Section: Introductionmentioning
confidence: 99%